Quercus infectoria Gall Extract Enhanced the Proliferation and Activity of Human Fetal Osteoblast Cell Line (hFOB 1.19) - Hapidin, Hermizi; Rozelan, Dalila; Abdullah, Hasmah; Wan Hanaffi, Wan Nurhidayah; Soelaiman, Ima Nirwana (2015)
Background: The present study investigated the effects of Quercus infectoria (QI) gall extract on the proliferation, alkaline phosphatase (ALP), osteocalcin, and the morphology of a human fetal osteoblast cell line (hFOB 1.19). Methods: The cells were cultured in Dulbecco’s modified eagle medium F12 supplemented with a 10% fetal bovine serum, a 1% penicillin/streptomycin and were treated with QI at various concentrations (0.1 to 99.0 μg/mL) for 72 hours. The levels of ALP and osteocalcin were measured at day 1, 3, 7, 10, and 14 and were compared among the negative control, pamidronate and QI groups. Results: The median effective concentration (EC50) of hFOB 1.19 treated with QI was 10.30 μg/mL. This concentration was more effective compared to the control drug, pamidronate (EC50 at 16.09 μg/mL). The ALP and osteocalcin levels of hFOB 1.19 treated with QI from day 7 and onwards were significantly increased in a time and concentration-dependent manner. Interestingly, from day 7 until day 14, the ALP and osteocalcin levels were highest in the cells treated with QI compared to the other two groups. The morphology of cells treated with QI was uniformly elongated, higher in number and over-confluent. Conclusion: After treatment with QI, cell proliferation enhanced and ALP and osteocalcin levels increased.